Behaviorism Approach: Julian Rotter's Theory And Its Reorientation In Addressing Students' Difficulties In Learning Arabic Language - Maksudin, Maksudin; Hania, Irfan (Ijaz Arabi Journal of Arabic Learning, 2024)
This study examines Julian Rotter's approach to behaviorism on the locus of control related to its application in learning Arabic. This study seeks to complement the shortcomings of previous studies that were not discussed, namely the behaviorism approach in learning Arabic from the perspective of Julian Rotter's theory. The theory of behaviors by Julian Rotter suggests that there are four aspects of Locus of Control, namely: potential behavior, expectations, values of reinforcing elements, and psychological situations. This research uses a qualitative approach with the literature review method. A literature review is a method of studying library sources to obtain research data. The results of this study show that all aspects of Locus of Control can be applied to motivate students further to learn Arabic. Regarding learning, locus of control can be an alternative to enrich perspectives in learning guidance procedures to address students' learning difficulties. This is inseparable from two factors influencing students' learning difficulties: internal (psycho-physical) and external (social) factors. Following the described findings, reorienting the locus of control in managing student learning difficulties systematically and comprehensively can be an expected format to help accurately diagnose students' learning difficulties so that programmed intervention steps can effectively assist students in solving their problems. The process includes case identification, problem identification, diagnosis, prognosis, remedial/referral, evaluation, and follow-up. All these stages are carried out by integrating the locus of control system